How to make money in any market - Cramer, Jim (Simon & Schuster, 2025)
"Renowned personal finance expert, bestselling author, host of CNBC's Mad Money, and cohost of Squawk on the Street Jim Cramer returns with how to make money in any market for every investor. Except for the one percent of the one percent, nobody learns how to make your money grow in the stock market. Jim Cramer has spent his career determined to change that. Now a household name after twenty seasons of Mad Money with Jim Cramer, cohost of Squawk on the Street, and host of CNBC's Investing Club, Cramer shows you how to get rich by understanding the market and investing in the right growth and income stocks--ones that he can help you identify. How to Make Money in Any Market is your guide to overcoming your fear about investing, to be able to make bigger money with what you have, no matter how small--in any market." --